Under pressure: Cassiopea andromeda jellyfish exposed to increasing water temperature or lead, cadmium and anthropogenic gadolinium contamination. Issue 1 (7th February 2022) - Béziat, Pauline; Kunzmann, Andreas
ABSTRACT: Similar to other cnidarians such as stony corals, the upside-down jellyfish ( Cassiopea spp . ) lives in endosymbiosis with dinoflagellates of the family Symbiodiniaceae. These jellyfish have been described as invasive species and are now found circumtropically in coastal marine environments. This study investigates the response of Cassiopea andromeda and its symbiotic algae to increased water temperature, further elucidating potential impacts of climate change on its populations in tropical ecosystems. It is demonstrated that water temperatures above 34°C are lethal for the C. andromeda medusae tested in this study. A non-lethal temperature rise triggers significant changes in the animals behaviour and physiology, including significant changes in bell pulsation rate and a significant decrease in photochemical efficiency, once 33°C is reached. Additionally, it is demonstrated that C. andromeda is capable of bioconcentrating significant amounts of cadmium from the surrounding water column. In the case of lead exposure, the jellyfish appear capable of regulating intake; no significant bioconcentration has been observed in this study. Our results do not indicate significant differences between the uptake patterns of anthropogenically complexed gadolinium chelates – emerging aquatic pollutants originating from hospital effluents – and the natural, non-chelated rare earth element terbium. This study supports the potential use of Cassiopea jellyfish as an attractive bioindicator species, serving to detect both continuous and pulse-contamination of coastal marine ecosystems. Cassiopea andromeda appears stable up until temperatures of about 34°C, suggesting that temperature increase concomitant with climate change might drive important range extensions of this tropical species into new environments – environments in which the holobiont will play significant roles in local pollutant dynamics.